2011
DOI: 10.1007/s13580-011-0012-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth and physiological responses of Chinese cabbage and radish to long-term exposure to elevated carbon dioxide and temperature

Abstract: Future forecasts for climate change predict the global mean surface air temperature rise by 1 -4 and double current atmospheric CO2 level before the end of 21 century. Increased atmospheric temperature and CO2 concentration are particularly important concerns for agricultural, horticultural and native plant production. In this study, effects of long-term exposure to elevated temperature and carbon dioxide (CO2) on the growth and physiological responses of 3 cultivars of Chinese radish (Raphanus sativus L.) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 43 publications
4
20
1
2
Order By: Relevance
“…The FvCB model has been used in a wide range of physiological studies on crop plants, from estimating the underlying C3 leaf biochemistry to predicting the photosynthetic fluxes of ecosystems in response to climate change (Yin & Struik, ). Previous long‐term studies on Kimchi cabbage exposed to elevated CO 2 showed a greater influence on photosynthesis (Choi et al., ; Lee et al., ), decreasing the net photosynthetic rate, stomatal conductance, and internal CO 2 concentration. Choi et al.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…The FvCB model has been used in a wide range of physiological studies on crop plants, from estimating the underlying C3 leaf biochemistry to predicting the photosynthetic fluxes of ecosystems in response to climate change (Yin & Struik, ). Previous long‐term studies on Kimchi cabbage exposed to elevated CO 2 showed a greater influence on photosynthesis (Choi et al., ; Lee et al., ), decreasing the net photosynthetic rate, stomatal conductance, and internal CO 2 concentration. Choi et al.…”
Section: Discussionmentioning
confidence: 83%
“…(Yin & Struik, 2009). Previous longterm studies on Kimchi cabbage exposed to elevated CO 2 showed a greater influence on photosynthesis (Choi et al, 2011;Lee et al, 2016), decreasing the net photosynthetic rate, stomatal conductance, and internal CO 2 concentration. Choi et al (2011) suggested that this might occur because decreases in photosynthesis at elevated CO 2 concentrations are associated with a decreased demand for carbohydrates.…”
Section: Morphological Features Of Hot Pepper Leaf Structurementioning
confidence: 77%
See 2 more Smart Citations
“…고랭지는 해발고도가 높아질수록 기온이 점차 낮아지는 기후 특 성 때문에 여름철에 고온다습으로 인해 평난지에서 재 배하기 어려운 호냉성 작물인 배추를 재배하기에 적합 하다. 고농도 CO 2 조건에서 배추의 광합성 특성과 생육 에 대하여는 봄배추나 가을배추 재배시 연구가 진행된 바 있으나 (Choi et al, 2011;Lee et al, 2006) (Marshall and Biscoe, 1980;Oh et al, 2015). (Farquhar et al, 1980 (Vuorinen et al, 2004;Piñero et al, 2014;Lee et al, 2009).…”
Section: 서 론unclassified